A Study of Several Financial Literacy Teaching Methods for Children - Jumadil Saputra; Dwi Susanti (International Journal of Ethno-Sciences and Education Research, 2021)
Financial literation is very important to be applied to the child as early as possible. Financial literation will be very influential to the understanding and knowledge about finance and also the level of prosperity in the future. This paper aims to discuss several ways to teach children the functions and uses of money, and how to manage finance. The methods examined include: giving allowance to children, teach children to have savings, bring children do shopping, teach children to share, teach children that it takes effort to earn money and teach finance with a simple understanding. The results showed that the introduction of the knowledge of financial literacy in early age make children accustomed to manage their financial in the future. Therefore, parents must be able to effectively carry out financial literacy to children from an early age.